On social facts - Gilbert, M; Margaret Gilbert (1978)
﻿ Four concepts are considered in relation to the question: can an illuminating characterization of the social sciences be given in terms of one concept of a relatively natural kind of thing? Weber's concept of 'social action' provides neither a general characterization, nor an important partial account, or so I argue after examining its relation to collectivity concepts, to suicide studies, and to standard desiderata for scientific concepts. I next assess the notion of 'meaningful'action. Peter Winch claims that such action is always 'social' in some sense, because it involves rule-following and rules f presuppose' a social setting. I consider the nature of Winch's Wittgensteinian arguments about rules; two senses in which all action might be 'social' emerge; however, were 'social actions' in either sense the focus of a science, it would not therefore aptly be called a social science, the senses of 'social' here being too weak. I turn next to what I allege is Durkheim's basic notion of a 'social fact' , roughly, that of a way of acting which 'inheres in' and is 'produced by' a social group. I present a highly articulated reconstruction of this notion: a 'collective practice', Pr, of a social group, G, will "be a 'Durkheimian social phenomenon', according to this revised conception, if and only if either Pr or another collective practice of G provides members of G who conform to Pr with a 'basic' reason for so conforming. A central element in my account of collective practices is a notion of 'group common knowledge' derived from David Lewis. I finally undertake a detailed critique of David Lewis's account of conventions and of the 'co-ordination problems' Lewis claims underlie conventions; I argue for a kind of account different in form from Lewis's, in which conventions are not, and do not necessarily involve, 'regularities' in behaviour. The Durkheimian notion is judged the best joartial characterization of a social science considered. Its presupposition of the notion of a social group is, I argue, no flaw. I conclude with a general theory of 'socialness', and hence of social science, based on my judgements about the four concepts considered.